ANALISIS KELAYAKAN USAHATANI NANAS (Ananas comosus Merr) DI DESA SIWARAK, KECAMATAN KARANGREJA, KABUPATEN PURBALINGGA (Studi Kasus Pada Kelompok Tani Barokah) - Widi Widayat; Pujiharto Pujiharto; Rahmi Hayati Putri (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2016)
Pineapple is a fruit crop shrubs from which has at scientific name Ananas comosus (L) Merr. The plant is easy to be cultivated because of both growing in wet or dry climates.The study aims to determine: the financial condition covered cost and revenues, feasibility of pineapple farming, pineapple farming sensitivity in the costs and revenue changes, the time required for break-even point, and the problem faced by farmer Siwarak village, Karangreja sub district, Purbalingga regency. The data obtained from direct interview to 58 pineapple farmers who were Barokah farmers group members. The result showed that : (1) The cost spent for a planting season was Rp.61.897.186,00 per 1 hectares, the income was Rp.205.649.177,00 per 1 hectrares, and the net income was Rp.143.751.991,00 per 1 hectares. (2) The feasibility analysis with discount level was 11.50% and NPV obtained Rp.90.457.173,00, IRR 95,82%, Net B/C ratio of 3.48, so declared feasible for business. (3) The sensitivity analysis by doing decline for cost 30%, the increase cost was 30% and a decrease in revenue of 30% as well as the increase cost was 30%, pineapple farming still feasible for business. (4) From the payback period analysis can be concluded that farmers could give break-even point in 2.61 years. (5) Farmers experiencing problem in meeting the needs of labor outside the family because at the sametime other farmers also need manpower to cultivate land.